2010
DOI: 10.3390/molecules15107083
|View full text |Cite
|
Sign up to set email alerts
|

Two New Alkaloids from Narcissus serotinus L.

Abstract: The Amaryllidaceae family is well known for the presence of an exclusive group of alkaloids with a wide range of biological activities. Narcissus serotinus L. is a plant belonging to this family and its geographical distribution is mainly located along the Mediterranean coast. In the present work, specimens collected near Casablanca (Morocco) were used to study the alkaloid content of this species. Starting with 350 g of the whole plant we used standard extraction and purification procedures to obtain fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 15 publications
(21 reference statements)
2
30
0
Order By: Relevance
“…[8] (20). The 1 H NMR, 13 C NMR, and infrared spectral data presented above were in good agreement with those reported for the natural product [7] and for the synthetically derived (À)-narseronine. [8] The only minor discrepancy was observed in the 13 C NMR spectra.…”
Section: -G]indol-7(1h)-one (19)supporting
confidence: 87%
See 2 more Smart Citations
“…[8] (20). The 1 H NMR, 13 C NMR, and infrared spectral data presented above were in good agreement with those reported for the natural product [7] and for the synthetically derived (À)-narseronine. [8] The only minor discrepancy was observed in the 13 C NMR spectra.…”
Section: -G]indol-7(1h)-one (19)supporting
confidence: 87%
“…Finally, treatment of compound 8 with (Ph 3 P) 4 Pd in the presence of dimedone resulted in cleavage of the Alloc group, thus allowing the resulting secondary amine 9 (which was not isolated) to undergo an intramolecular hetero-Michael addition reaction/ trans-acylation sequence and so affording (À)-narseronine [(À)-1] (82 %), the structure of which was secured by singlecrystal X-ray analysis. Unfortunately, the specific rotation for the natural product obtained by Bastida et al [7] was not reported and so it has not been possible to establish its absolute configuration.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, extracts were subjected to a combination of chromatographic techniques and alkaloids identified by GC-MS and NMR (16,17). In order to be able to segregate the order of milligrams of product, the corresponding scale-up attending to the required proportion was made as described (19,20).…”
Section: Collection Of Purified Alkaloid Compounds From Amaryllidaceamentioning
confidence: 99%
“…In some related studies we have been able to establish a synthesis of narseronine (45), an alkaloid isolated recently from the flowering plant Narcissus serotinus L. that grows in dry coastal regions of many parts of the Mediterranean [26]. Perhaps the most notable structural feature of the compound is the presence of an unsaturated δ-lactone residue within the B-ring.…”
Section: Cis-12-dihydrocatechols As Precursors To Lycorinine Alkaloidsmentioning
confidence: 99%